Institutional Adaptation through Integrated Curriculum Management and Multiple Intelligences at a Modern Islamic Boarding School - Abdillah, Silmi Syahidatun Nisa; Inayati, Nurul Latifatul Inayati (Jurnal Sosiologi Agama Indonesia (JSAI), 2025)
Islamic  boarding schools (pesantren) face the continuing challenge of maintaining a distinctive religious ethos while responding to contemporary educational demands shaped by digitalisation and changing public expectations. This study examines how integrated curriculum management at Imam Syuhodo Modern Islamic Boarding School in Central Java supports institutional adaptation by coordinating curriculum planning, implementation, supervision, and evaluation within a single governance arrangement. Using a qualitative case study design, data were collected through in-depth interviews with key institutional actors, participatory observation over three months, and document analysis. Data were analysed using the Miles, Huberman, and Saldaña interactive model to identify recurring patterns in organisational routines and educational practices. The findings show that collaborative planning enables the institution to negotiate the national Kurikulum Merdeka with pesantren theological priorities through structured decision-making and agreed time allocation for religious learning. Implementation reflects an inclusive curriculum orientation informed by Multiple Intelligences assumptions, enacted through multimodal classroom practices, structured organisational training, dormitory leadership roles, and student-managed units such as the Green House and Shofiyah Canteen. Sustainability is supported through developmental academic supervision that emphasises dialogic feedback and informs annual curriculum revision, reinforcing an organisational learning cycle. Interview accounts also indicate that leaders frame digital literacy through ethical guidance referred to as adab digital, positioning technology use within Islamic moral commitments. This study suggests that integrated curriculum governance can support inclusive learning pathways and institutional adaptation in a modern pesantren context, while future research should compare multiple sites and examine longer-term outcomes.